Synthesis and Characterization of Biologically Active 1-(Substituted Aminomethyl)-3-(3'-bromo-4'-methoxybenzoylhydrazono)indolin-2-ones - H. Havaldar, Freddy; Kumar J. Mishra, Sushil (Asian Journal of Chemistry, 2016)
3-Bromo-4-methoxybenzoyl hydrazine (1) was condensed with indole-2,3-dione in ethanol to yield 3-(3'-bromo-4'-methoxybenzoylhydrazono)indolin-2-one (2) which on aminomethylation with formaldehyde and different amines furnished 1-(substituted aminomethyl)-3-(3'-bromo-4'-methoxybenzoylhydrazono)indolin-2-ones (3a–e). The structures of the newly synthesized compounds have been established by analytical and spectral methods. These compounds have shown promising biological activity.